KARAKTERISTIK DISMENORE PADA PASIEN ENDOMETRIOSIS DI RSUD DR. SOETOMO SURABAYA - Ariviani, Fauziah; Annas, Jimmy Yanuar; Sari, Gadis Meinar (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
ABSTRACT Endometriosis is a disordered growth of the endometrial glands outside the uterus that often affects women of reproductive age. Endometriosis could reduce the quality of life and prone to bear the infertility. The most common symptom is dysmenorrhea, and this is often times misunderstood by most of women who thought menstruating women commonly experienced this. The purpose of the research is to determine the characteristics of dysmenorrhea in endometriosis patients. This research was an observational study by conducting direct interview with patients and analyzing descriptively. There are 42 respondents in this research, the highest frequencies in variable were as follows: age diagnosed is 30-39 years (42.8%), age of dysmenorrhea onset is 2 days (66.7%), pain intensity on a scale of 8 (33.3%), and the pain description is like squeezing (61.9%). In this research the average delay in diagnosis of endometriosis for 10.6 years, patients begin experiencing dysmenorrhea during menstruation for more than two days, the pain intensity of dysmenorrhea is on a scale of 8, and the pain description is like squeezing.